Multiinstrument Studies of Thermospheric Weather Above Alaska. Issue 11 (24th November 2018) - Conde, M. G.; Bristow, W. A.; Hampton, D. L.; Elliott, J.
Abstract: We describe how space weather impacts thermospheric winds above Alaska, using an array of ground and space‐based instrumentation. Forcing of the thermosphere is observed using coherent (Super Dual Auroral Radar Network) and incoherent (Poker Flat Incoherent Scatter Radar) radars to measure ion convection, plus ground and space‐based imagers to map auroral precipitation. The primary emphasis in this work is to determine the neutral thermospheric wind response at F  region heights to these drivers, using an array of ground‐based all‐sky imaging Fabry‐Perot spectrometers that record Doppler spectra of optical emissions at 630‐nm wavelength, originating from a height of around 240 km. Line‐of‐sight winds are derived from Doppler shifts and, because each instrument only directly measures this one component, considerable postprocessing must be applied to infer the full three‐component vector velocity field. Several techniques for doing so are identified, and a detailed description is presented of the hybrid algorithm used here. Results show that thermospheric winds at these latitudes respond strongly to magnetospheric drivers associated with the aurora over length scales down 100 km or less, and on time scales as short as 15 min. These scales are considerably smaller than those resolved by previous observations, or those captured in semiempirical models such as the Horizontal Wind Model or global‐scale first principle models such as the Thermospheric Global Circulation Model and its relatives. Divergence and vorticity commonly occur in the observed horizontal wind fields, over regions spanning hundred of kilometers across and with magnitudes exceeding 0.5 × 10 − 3 s −1 . Plain Language Summary: This article combines data from multiple instruments to show how Earth's aurora and flows of ionosphere plasma perturb winds in the neutral atmosphere at 240‐km altitude. It shows how atmospheric weather at this height is driven by space weather. Key Points: Multiple intruments are used together to study space weather drivers of disturbances in Earth's thermosphere Strong localized coupling occurs between neutral and ion flows Instruments and techniques are described for mapping thermospheric neutral wind fields